Impact of macroeconomic indicators on public debt of Slovak Republic - Knapková, Miroslava; Kiaba, Martin; Hudec, Samuel (Journal of Business Economics and Management, 2019)
The paper focuses on impact of macroeconomic indicators on the development of public debt in Slovakia. The aim of the paper was to identify those macroeconomic indicators which influence the most significantly public debt in Slovakia and to elaborate and verify simple model for public debt prediction. Research was based on the analysis of chosen macroeconomic indicators. Selection of macroeconomic indicators resulted from theoretical knowledge and study of various research papers. Authors used several scientific methods, such as content-causal analysis, comparison, mathematical and statistical methods, including simple linear regression. Macroeconomic indicators, which authors proved to be statistically significant, are GDP growth rate, openness of economy, size of public sector, government bond yields, and unemployment rate. Authors elaborated model of the public debt development in Slovakia by using a simple linear regression model. Regression model was calculated using the data for 1995-2016. Authors confirmed correctness of the model by using data for 2017. Research was limited by the fact, that there are limited data available for analysis (time series of 22 years) because of short existence of independent Slovakia. It will be necessary to continue with the research and to verify correctness of chosen indicators in longer period.